EXPERIMENTAL RESEARCH ON MECHANICAL PROPERTIES OF TITANIUM ALLOY AIRCRAFT STRUCTURE MAINTENANCE PARTS BY ADDITIVE MANUFACTURING - LIU ShiHua; ZHANG BaoCai; XIE SuiJie; CHENG ZongHui; ZHANG Jie; LI HaiCheng (Jixie qiangdu)
In order to comprehensively evaluate the feasibility of the engineering application of titanium alloy, the comparative investigations on mechanical performances including the fatigue performance of both aircraft structural maintenance parts and material were carried out based on the different processing methods in which titanium alloy and typical structural samples were respectively made by the selective laser melting(SLM) and traditional mechanical process. As the results, the tensile, shear, and impact properties of titanium alloy by SLM method were excellent at room temperature, and the relative error of various mechanical properties is less than 10% when compared with titanium alloy plates by mechanical process. The aforementioned typical structural samples manufactured by SLM also have the strongest performance of mechanical processing, the relative error of static strength is less than 5%, and the maximum relative error of fatigue strength is 12.9%, titanium alloy typical structural parts manufactured by SLM also have the same level performance of mechanical processing. The reinforcement effect of titanium alloy aircraft structural maintenance parts manufactured by SLM is equivalent to or even slightly better than that of high strength steel by mechanical process. The research shows that the titanium alloy structure made by SLM also meets the basic installation requirement and use.